Effects of Korean black raspberry supplementation on oxidative stress and plasma antioxidant capacity in healthy male smokers. (June 2015) - Park, Eunkyo; Cho, SooMuk; Lee, Jung eun; Lee, Seung Min; Kim, Yesl; Go, Min-Sun; Kim, Young-Jae; Jung, In-Kyung; Auh, Joong Hyuck; Choi, Hyung-Kyoon; Kim, Jung-Hyun
Highlights: Korean black raspberry (BR) supplementation was investigated for antioxidant effect in healthy male smoker. Four weeks of BR supplementation reduced lipid peroxidation. BR provided high amounts of exogenous antioxidants including anthocyanin. BR supplementation enhanced endogenous antioxidant enzyme activities, glutathione peroxidase and catalase. BR supplementation could reduce smoking-induced oxidative stress by enhancing endogenous antioxidant activities in plasma. Abstract: Oxidative stress has been implicated in the pathophysiology of chronic diseases and cigarette smoking is known to be one of the major sources of oxidants. In this study, we investigated whether Korean black raspberry (BR) supplementation could reduce smoke-induced oxidative stress in healthy male smokers. Thirty nine healthy male smokers received either 30 g of freeze-dried BR or placebo for four weeks. Anthropometric and dietary data, smoking history, blood lipid profiles, lipid peroxidation, DNA damage, and antioxidant enzyme activities were assessed at baseline and after supplementation. There was no difference of age, smoking history, anthropometry, and nutrient intake between groups. BR supplementation had no effect on plasma lipid profiles, LDL oxidation, and DNA damage. However, it significantly increased the activity of the antioxidant enzymes, glutathione peroxidase and catalase, and reduced plasma lipid peroxidation. In conclusion, BR supplementation may decrease cigarette smoke-induced oxidative stress through increase of endogenous antioxidant enzyme activities.